2008
DOI: 10.1111/j.1600-6143.2007.02144.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hemi-Portocaval Shunt Based on Portal Vein Pressure for Small-for-Size Graft in Adult Living Donor Liver Transplantation

Abstract: We developed an algorithm of graft selection in which left lobe donation is considered primarily if the graftto-recipient weight ratio (GRWR) is estimated to be greater than 0.6% in preoperative volumetry with utilization of a hemi-portocaval shunt (HPCS) based on portal vein pressure (PVP) more than 20 mmHg at the time of laparotomy. A total of 11 consecutive adult living donor liver transplantations with small-forsize graft according to our graft selection algorithm were performed between December 2005 and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 34 publications
5
103
0
2
Order By: Relevance
“…In such cases, even grafts with a GRWR <0.6 can be transplanted successfully (11,13,14). In case of portal hypertension, different surgical techniques are available to reduce or eliminate the rate of postoperative complications related to the small-forsize syndrome (SFSS) (12,16). The signs of SFSS observed in our patients with hyperbilirubinemia could obviously be related to a small graft volume.…”
Section: Discussionmentioning
confidence: 86%
“…In such cases, even grafts with a GRWR <0.6 can be transplanted successfully (11,13,14). In case of portal hypertension, different surgical techniques are available to reduce or eliminate the rate of postoperative complications related to the small-forsize syndrome (SFSS) (12,16). The signs of SFSS observed in our patients with hyperbilirubinemia could obviously be related to a small graft volume.…”
Section: Discussionmentioning
confidence: 86%
“…Although portal inflow modulation has been reported to prevent SFSS, (33)(34)(35)(36) the role of modulation remains controversial. (37,38) We previously reported that small graft size is associated with high PVP and that high PVP (25 mm Hg) is correlated with posttransplant thrombocytopenia, (39) but we have not performed any portal inflow modulation because there has not been a recipient with high PVP since that study.…”
Section: Discussionmentioning
confidence: 99%
“…27 Another study showed excellent graft survival in recipients of left lobe grafts with graft-to-recipient weight ratio between 0.6 and 0.8. 28 The main concern in using small-for-size grafts is the problem of small-for-size syndrome, which can cause graft loss and necessitate revision transplant.…”
Section: Discussionmentioning
confidence: 99%